Polyvinyl alcohol polymer
The polyvinyl alcohol-based polymer prepared by copolymerizing vinyl ester monomers and multifunctional monomers solves the problem of poor fluid loss reduction effect under high temperature and high pressure conditions, and achieves improved solubility and fluidity at high temperatures. Suitable for oil well cement additives.
Patent Information
- Application Number
- CN202380042583.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-08
- Filing Date
- 2023-05-24
- Publication Date
- 2025-01-07
AI Technical Summary
The existing polyvinyl alcohol-based polymers are dissolved and dissolution under high temperature and high pressure conditions, resulting in a decrease in the effect of reducing fluid loss, and increasing the addition amount cannot solve the problems of reduced fluidity and increased cost.
Polyvinyl alcohol-based polymers were prepared by saponification of vinyl ester monomers and a copolymer containing two or more polymerizable unsaturated bonds in the molecule, and their average polymerization degree and polymerizable unsaturated bond reaction rate were controlled. and multifunctional monomers to form polymers with advanced polymer structures, ensuring that the swelling state is maintained at high temperatures and reducing fluid losses.
Excellent fluid loss reduction effect under harsh conditions is achieved, the formation of adhesions that are insoluble in solvents is avoided, and the fluidity of cement slurry is improved without increasing viscosity.
Smart Images

Figure BDA0005150575890000151 
Figure BDA0005150575890000161
Abstract
Description
Technical Field
[0001] The present invention relates to a polyvinyl alcohol polymer, and its application and preparation method. Background Art
[0002] Polymers having a polyvinyl alcohol (PVA) skeleton (hereinafter, collectively referred to as "polyvinyl alcohol-based polymers", "vinyl alcohol-based polymers" or simply "PVA") are known as hydrophilic synthetic resins, and various uses that utilize their properties are continuously being developed.
[0003] As one of such uses, additives in oil well cement used in cementing of oil wells, gas wells, steam wells for geothermal power generation, etc. can be cited. Oil well cement is filled into the gap between the steel pipe and the pit in the form of a slurry mixed with water and other additives to fix and protect the steel pipe (casing). Therefore, the cement slurry preferably has high fluidity so that it is easy to fill. Here, the phenomenon of losing water contained in the cement slurry due to high pressure during injection and underground heat is generally referred to as "fluid loss". Due to fluid loss, the fluidity of the cement slurry is reduced, resulting in poor cementing and poor hardening after cement hardening. Therefore, a fluid loss reducer is usually added to the slurry of oil well cement.
[0004] As such a fluid loss reducing agent, it has been proposed to use a polyvinyl alcohol-based polymer as a main component. For example, Patent Documents 1 and 2 describe PVA used in a fluid loss reducing agent.
[0005] However, in recent years, the exploitation of shale gas wells in particular has become more and more in-depth, so the conditions of pressure and temperature are becoming more and more severe. For the above-mentioned previous fluid loss reducers containing PVA, the fluid loss reduction performance required by the cement slurry injected under such severe conditions of high temperature and high pressure has not yet been achieved. Specifically, the fluid loss reducer of the PVA system dissolves at high temperatures, and if it is further dissolved into the pit under high pressure conditions, the result is that the fluid loss reduction effect decreases. Therefore, the solubility resistance of the fluid loss reducer of the PVA system at high temperatures is required. In addition, even if you want to increase the addition amount of the previous fluid loss reducer, you can't solve the problems of reduced fluidity and increased costs caused by the cement slurry viscosity increase by increasing the amount.
[0006] In order to solve the above problems, Patent Document 3 discloses an oil well cement additive containing a vinyl alcohol polymer, which is a saponified copolymer of a vinyl ester monomer and a multifunctional monomer, having a saponification degree of 70 to 95 mol % and a viscosity average degree of polymerization of 1000 to 10000.
[0007] In addition, Patent Document 4 discloses a polyvinyl alcohol polymer obtained by saponifying a homopolymer of a vinyl ester monomer, a copolymer of a vinyl ester monomer and a monofunctional monomer other than vinyl ester, a copolymer of a vinyl ester monomer and a polyfunctional monomer, or a copolymer of a vinyl ester monomer and a monofunctional monomer other than vinyl ester and a polyfunctional monomer, characterized in that the particle size distribution of a 0.4 mass % aqueous solution of the polyvinyl alcohol polymer obtained by dynamic light scattering measurement at a temperature of 25° C. has a cumulative frequency of 50% of a particle size of 50 nm or more.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: International Publication No. 2007 / 146348
[0011] Patent Document 2: Japanese Patent Application Publication No. 2015-196733
[0012] Patent Document 3: International Publication No. 2019 / 163490
[0013] Patent Document 4: International Publication No. 2022 / 024792 Summary of the invention
[0014] Problems to be solved by the invention
[0015] However, the following problem was discovered for the first time: in the conventional polymerization reaction of a multifunctional monomer and a vinyl ester monomer, a crosslinked product is generated during the polymerization, and an adhering substance insoluble in a solvent is generated in the system.
[0016] Means for solving problems
[0017] In order to solve the above-mentioned problems, the present invention can provide the following solutions.
[0018] A polyvinyl alcohol polymer characterized in that it is obtained by saponifying a copolymer of a vinyl ester monomer and a multifunctional monomer having two or more polymerizable unsaturated bonds in the molecule.
[0019] The average degree of polymerization of the polyvinyl alcohol-based polymer measured by the method described in JIS K 6726:1994 is 3000 to 6000.
[0020] The reaction rate of the polymerizable unsaturated bonds of the polyfunctional monomer is 55 to 75%.
[0021] In another embodiment, the number of polymerizable unsaturated sites of the polyfunctional monomer may be 2 to 5. In another embodiment, the amount of polymerizable unsaturated sites of the polyvinyl alcohol polymer may be 0.05 to 0.30 mol% relative to the total of the vinyl alcohol unit and the vinyl acetate unit. In another embodiment, the amount of the polyfunctional monomer unit of the polyvinyl alcohol polymer may be 0.05 to 0.30 mol% relative to the total of the vinyl alcohol unit and the vinyl acetate unit.
[0022] In another embodiment, the viscosity of a 4% aqueous solution of the polyvinyl alcohol-based polymer may be 40 to 200 mPa·s, and the degree of saponification may be 75 to 99 mol%.
[0023] In another embodiment, the filter pass rate of the 1.0 mass % aqueous solution of the polyvinyl alcohol-based polymer with a mesh size of 45 μm can be 95 mass % or more in terms of solid content conversion, and the membrane filter pass rate of the 1.0 mass % aqueous solution of the polyvinyl alcohol-based polymer with a pore size of 0.45 μm can be 5 mass % or less in terms of solid content conversion. In another embodiment, with respect to the particle size of the polyvinyl alcohol-based polymer, the polyvinyl alcohol-based polymer with a particle size of 75 μm or less can be 20 mass % or less, and the polyvinyl alcohol-based polymer with a particle size of 500 μm or more can be 10 mass % or less.
[0024] In another embodiment, an additive for oil well cement containing the polyvinyl alcohol polymer can be provided. In another embodiment, a method for producing the polyvinyl alcohol polymer can be provided. These embodiments can be combined in any manner as long as they are not contradictory.
[0025] Effects of the Invention
[0026] The polyvinyl alcohol polymer according to the present invention can suppress the generation of solvent-insoluble deposits during the production process and exhibits an excellent fluid loss reduction effect even under severe high-temperature or high-pressure environments. DETAILED DESCRIPTION
[0027] The following is a description of a specific embodiment of the present invention. It should be noted that the embodiment described below is an example of an embodiment of the present invention, and the scope of the present invention is not to be interpreted narrowly. Unless otherwise specified, the numerical range in this specification includes its upper limit and lower limit. The polymer in this specification refers to the definition of polymer by the Polymer Nomenclature Committee of the International Union of Pure and Applied Chemistry (IUPAC), that is, "a polymer molecule refers to a molecule with a large relative molecular mass, and has a structure composed of multiple repetitions of units substantially or conceptually obtained from molecules with a small relative molecular mass".
[0028] <Chemical Structure of Polyvinyl Alcohol-Based Polymer>
[0029] The polyvinyl alcohol polymer of the present invention is a polymer obtained by saponifying a homopolymer of a vinyl ester monomer, a copolymer of a vinyl ester monomer and a monofunctional monomer other than vinyl ester, a copolymer of a vinyl ester monomer and a multifunctional monomer, or a copolymer of a vinyl ester monomer and a monofunctional monomer other than vinyl ester and a multifunctional monomer. The polyvinyl alcohol polymer of the present invention has an advanced polymer structure different from conventional PVA, and can therefore maintain a swollen state at high temperatures. As described below, the presence of such a polymer structure can be confirmed by an average degree of polymerization of 3000 to 6000 as measured by the method described in JIS K 6726:1994 and a reaction rate of polymerizable unsaturated bonds of 55 to 75% of the multifunctional monomer.
[0030] <Raw Material Components of Polyvinyl Alcohol-Based Polymer>
[0031] As the vinyl ester monomer, for example, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, etc. may be used, and a mixture thereof may also be used. From the viewpoint of ease of polymerization, vinyl acetate is preferred.
[0032] In addition, as monofunctional monomers copolymerizable with vinyl ester monomers (i.e., monofunctional monomers other than vinyl esters), for example, the following compounds can be cited. α-Olefin monomers such as ethylene and propylene. (Meth)acrylic acid alkyl ester monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Unsaturated amide monomers such as (meth)acrylamide and N-hydroxymethyl acrylamide. Unsaturated carboxylic acid monomers such as (meth)acrylic acid, crotonic acid, maleic acid, itaconic acid, and fumaric acid. Alkyl (methyl, ethyl, propyl, etc.) ester monomers of unsaturated carboxylic acids. Anhydrides of unsaturated carboxylic acids such as maleic anhydride. Sodium, potassium, ammonium, etc. salts of unsaturated carboxylic acids. Sulfonic acid group-containing monomers such as 2-acrylamide-2-methylpropanesulfonic acid or their salts. Alkyl vinyl ether monomers.
[0033] In addition, as a multifunctional monomer copolymerizable with a vinyl ester monomer, a compound having two or more polymerizable unsaturated bonds in the molecule can be used. The number of polymerizable unsaturated sites of the multifunctional monomer is preferably 2 to 5. For example, the following compounds can be cited. Divinyl ethers such as ethylene glycol divinyl ether, propanediol divinyl ether, butanediol divinyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, polyethylene glycol divinyl ether, propylene glycol divinyl ether, polypropylene glycol divinyl ether, and divinyl sulfonic acid compounds. Diene compounds such as pentadiene, hexadiene, heptadiene, octadiene, nonadiene, and decadiene. Diallyl ether compounds such as glycerol diallyl ether, diethylene glycol diallyl ether, ethylene glycol diallyl ether, triethylene glycol diallyl ether, polyethylene glycol diallyl ether, trimethylolpropane diallyl ether, and pentaerythritol diallyl ether. Triallyl ether compounds such as glycerol triallyl ether, trimethylolpropane triallyl ether, and pentaerythritol triallyl ether. Tetraallyl ether compounds such as pentaerythritol tetraallyl ether. Multifunctional monomers containing allyl ester groups such as diallyl phthalate, diallyl maleate, diallyl itaconate, diallyl terephthalate, and diallyl adipate. Diallylamine compounds such as diallylamine and diallylmethylamine, and multifunctional monomers containing allylamino groups such as triallylamine. Multifunctional monomers containing an allyl ammonium group such as diallyl ammonium salts such as diallyl dimethyl ammonium chloride. Multifunctional monomers containing two or more allyl groups such as triallyl isocyanurate, 1,3-diallyl urea, triallyl phosphate, and diallyl disulfide. Multifunctional monomers containing (meth)acrylic acid such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, glycerol di(meth)acrylate, glycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and isocyanuric acid tri(meth)acrylate. Polyfunctional monomers having (meth)acrylamide such as N,N'-methylenebis(meth)acrylamide and N,N'-ethylenebis(meth)acrylamide. Polyfunctional aromatic monomers such as divinylbenzene and trivinylbenzene. Polyfunctional monomers containing glycidyl groups such as allyl glycidyl ether and glycidyl (meth)acrylate.
[0034] From the viewpoint of reactivity with vinyl ester monomer and difficulty in decomposition in saponification reaction, as a monomer copolymerizable with vinyl ester monomer, a compound having a carbonyl group or an amide group in the molecule is preferred, and a compound that is not easily decomposed in alkali is further preferred. In a preferred embodiment, PVA is obtained by saponifying a copolymer of a vinyl ester monomer and a multifunctional monomer, so that a cross-linked structure is formed by the multifunctional group, thereby having the effect of obtaining solubility resistance at high temperature. As such a multifunctional monomer, a compound having a ring structure is preferred, a compound having a heterocyclic structure is more preferred, and triallyl isocyanurate (TAIC) is particularly preferred.
[0035] <Average degree of polymerization>
[0036] The average degree of polymerization of the polyvinyl alcohol polymer measured by the method described in JIS K 6726:1994 "3.7 Average degree of polymerization" is 3,000 to 6,000, preferably 3,000 to 5,500, and more preferably 3,000 to 5,000.
[0037] <Calculation Method of Reaction Rate of Polymerizable Unsaturated Bond>
[0038] The reaction rate (consumption rate) of the polymerizable unsaturated bonds of the polyfunctional monomers in the polyvinyl alcohol-based polymer is in the range of 55 to 75%, preferably in the range of 55 to 73%. 1 H-NMR, 13 For example, when using NMR, the comonomer modification amount and the residual unsaturation amount can be calculated according to the following procedure, and the reaction rate can be derived from them.
[0039] <Copolymerization Amount>
[0040] In the case of copolymerizing the vinyl ester monomer and the monomers other than the vinyl ester, the amount of the structural unit derived from the monomers other than the vinyl ester is preferably 0.001 to 1.0 mol%, more preferably 0.005 to 0.5 mol%, and still more preferably 0.01 to 0.2 mol%, relative to 100 mol% of the structural unit derived from the vinyl alcohol unit in the vinyl alcohol polymer. By adjusting the copolymerization amount to such a range, the solubility resistance at high temperature is improved, and the vinyl alcohol polymer is not excessively crosslinked, which is also preferred from the viewpoint of production.
[0041] In addition, the amount of polymerizable unsaturated sites in the present polyvinyl alcohol polymer relative to the total of the vinyl alcohol unit and the vinyl acetate unit is preferably 0.05 to 0.30 mol%, and more preferably 0.10 to 0.30 mol%. In addition, the amount of polyfunctional monomer units in the present polyvinyl alcohol polymer relative to the total of the vinyl alcohol unit and the vinyl acetate unit is preferably 0.05 to 0.30 mol%, and more preferably 0.10 to 0.30 mol%.
[0042] <Comonomer Modification Amount>
[0043] The copolymerization amount (modification amount of the copolymerized monomer) of the PVA can be used in a solvent such as deuterated water or deuterated dimethyl sulfoxide. 1 H-NMR, 13 C-NMR or a trace total nitrogen analyzer. For example, when a trace total nitrogen analyzer "TN-2100H" (manufactured by Nittoseiko Analytech) is used, the calculation can be performed according to the following procedure.
[0044] The sample of the vinyl alcohol polymer was collected on a quartz plate, which was set in an autoboat controller "ABC-210" (manufactured by Nittoseiko Analytech Co., Ltd.) and automatically inserted into an electric furnace to be burned in an argon / oxygen flow. The NO gas generated at this time was measured using a chemiluminescence detector. A standard curve was prepared in advance using a standard solution (N-pyridine / toluene), and the nitrogen concentration was calculated based on the standard curve.
[0045] Example of measurement conditions
[0046] Reaction tube: double tube for ABC
[0047] Electric furnace temperature
[0048] Inlet Temp: 800°C, Outlet Temp: 900°C
[0049] Gas flow rate: Ar: 300mL / min, O2: 300mL / min, Ozone: 300mL / min
[0050] Sample volume: about 9-15 mg
[0051] <Calculation of Residual Unsaturation Amount>
[0052] The polyvinyl alcohol polymer was dissolved in heavy water and NMR (ECX-400 manufactured by JEOL Ltd.) was used to obtain the 1 The structure was identified by H-NMR spectrum.
[0053] The unsaturation content (mol%) in the polyvinyl alcohol polymer can be calculated based on the integrated value of the peak derived from the unsaturation, based on the integrated value of the peak derived from the methylene group in the main chain of the vinyl alcohol unit and the methylene group in the main chain of the vinyl acetate unit (1.8 to 2.5 ppm) of the polyvinyl alcohol polymer. 1 In the H-NMR spectrum, if the integral value of the methylene group of the main chain derived from the vinyl alcohol unit and the methylene group of the main chain derived from the vinyl acetate unit is set to b, and the integral value of the unsaturated bond derived from the polyfunctional monomer containing two or more unsaturated bonds is set to a (for example, in the case of triallyl isocyanurate, it is the peak near 6.3 ppm derived from -CH= of the allyl group), considering the number of protons on the carbon (2 for the methylene group and 1 for the allyl group), the residual unsaturation amount X (mol %) can be calculated as X={a / (b / 2+a)}*100.
[0054] <Calculation of Reaction Rate of Polymerizable Unsaturated Bonds in Polyfunctional Monomers>
[0055] The reaction rate of the polymerizable unsaturated bonds of the multifunctional monomer can be calculated from the modification amount and the residual unsaturation amount of the comonomer of the vinyl alcohol polymer. Specifically, the reaction rate Y (%) of the polymerizable unsaturated bonds can be calculated as Y = {[{(1-n) / modification amount of the comonomer*(n-1)}*(residual unsaturation amount)+n] / n}*100. Here, n in the formula is the number of polymerizable unsaturated bonds of the multifunctional monomer.
[0056] <Saponification degree>
[0057] In this specification, the saponification degree of PVA can be measured by the method described in Japanese Industrial Standard JIS K6726:1994 "3.5 Saponification Degree". The saponification degree of the polyvinyl alcohol polymer is preferably 75 to 99 mol%, more preferably 77 to 97 mol%, and even more preferably 79 to 95 mol%.
[0058] <Particle Size Distribution>
[0059] The particle size distribution of the present PVA particles can be quantified by dynamic light scattering measurement of a 0.4 mass % aqueous solution (diluted aqueous solution) of PVA at a temperature of 25°C. The particle diameter at which the cumulative frequency of the particle size distribution of the PVA particles is 50% is preferably greater than 50 nm, more preferably in the range of 70 to 1000 nm. It should be noted that the cumulative frequency is obtained based on the scattering intensity distribution frequency obtained by dynamic light scattering measurement.
[0060] The average particle size of PVA in the dilute aqueous solution can be set according to the application, for example, preferably 60 to 2000 nm, more preferably 70 to 1500 nm. It should be noted that the average particle size of PVA in the dilute aqueous solution in this specification can be obtained by cumulative analysis of the particle size distribution obtained by dynamic light scattering measurement of a 0.4 mass % aqueous solution of PVA at a temperature of 25°C.
[0061] When used as an additive for oil well cement, if the average particle size of PVA in the dilute aqueous solution is 60 nm or more, the PVA in the cement slurry becomes less likely to flow out, and the fluid loss reduction performance is improved, so it is preferred. If the average particle size of PVA in the dilute aqueous solution is 2000 nm or less, it is preferred from the perspective of productivity.
[0062] From the perspective of the strength of the cement after hardening and the production of PVA, the PVA particles preferably do not contain excessively large gel particles. More specifically, the filter pass rate of a 1.0 mass % aqueous solution of PVA through a 300 mesh (mesh size 0.045 mm) is preferably 95 mass % or more, more preferably in the range of 97 to 100 mass %, calculated as solid content.
[0063] Here, the filter pass rate of 300 mesh can be calculated according to the following steps. Dissolve the dried PVA in water at 25°C to obtain an aqueous solution with a concentration of 1.0 mass%. Filter 100 mL of the obtained PVA aqueous solution using a 300 mesh (mesh size 0.045 mm) filter and measure the mass of PVA remaining on the filter. Calculate the proportion of PVA that passes through the filter based on the mass of the measured PVA residue.
[0064] In addition, from the viewpoint of solubility resistance, the PVA particles are preferably of a particle size distribution that is not easy to pass through a membrane filter with a pore size of 0.45 μm. More specifically, the permeability of a 1.0 mass % aqueous solution of PVA through a membrane filter with a pore size of 0.45 μm is preferably 10 mass % or less, more preferably in the range of 0 to 5 mass %, calculated as solid content.
[0065] Here, the pass rate of a 0.45 μm membrane filter can be calculated according to the following steps. Using a 0.45 μm filter (manufactured by ADVANTEC, material: mixed cellulose ester, pore size: 0.45 μm, diameter 47 mm), a PVA aqueous solution adjusted to a concentration of 1.0 mass % was filtered for 10 minutes under reduced pressure (10 mmHg). The pass rate was calculated based on the amount of solid content in the filtrate.
[0066] With regard to the particle size of the present polyvinyl alcohol polymer, the polyvinyl alcohol polymer having a particle size of 75 μm or less (under a 75 μm sieve) is preferably 20% by mass or less, more preferably 18% by mass or less. In addition, the polyvinyl alcohol polymer having a particle size of 500 μm or more (on a 500 μm sieve) is preferably 10% by mass or less, more preferably 5% by mass or less. In a more preferred embodiment, the polyvinyl alcohol polymer having a particle size of 75 μm or less may be 20% by mass or less and the polyvinyl alcohol polymer having a particle size of 500 μm or more may be 10% by mass or less.
[0067] <Viscosity>
[0068] In this specification, the viscosity of the polyvinyl alcohol polymer can be measured by the method described in JIS K6726:1994 "4.2 Determination of viscosity". From the viewpoint of improving productivity, the viscosity is preferably in the range of 40 to 200 mPa.s, more preferably in the range of 50 to 160 mPa.s.
[0069] <Manufacturing method>
[0070] In the embodiment of the present invention, when polymerizing the vinyl ester monomer or its copolymer, a method of performing polymerization in two stages as described below can be used. By performing polymerization in two stages in this way, an effect of not easily leaving insoluble attachments in the system can be obtained. That is, first, an initiator is added to a mixture of the vinyl ester monomer and a multifunctional monomer having two or more unsaturated bonds in the molecule, and a first polymerization reaction is performed in an organic solvent until a first polymerization rate is reached. The first polymerization rate can be, for example, in the range of 5 to 60%, preferably in the range of 10 to 55%.
[0071] After the first polymerization reaction is completed, an organic solvent (which may be the same organic solvent or a different organic solvent) is further added, and a second polymerization reaction is further performed until a second polymerization rate is reached. The second polymerization rate is a value higher than the first polymerization rate, for example, it can be in the range of 10 to 65%, preferably in the range of 15 to 60%. As the organic solvent, alcohol can be preferably used. As the alcohol, for example, methanol, ethanol, butanol, etc. can be used, and methanol can be preferably used. The concentration of the polymer in the solution of the organic solvent can be arbitrarily set, for example, it can be 10% by mass or more and 80% by mass or less.
[0072] After the second polymerization reaction is completed, the unreacted vinyl ester monomer is discharged from the polymerization system, and the obtained polymer (polyvinyl ester, etc.) solution is saponified by any method, thereby preparing PVA. As an example of a saponification method, a method of adding an alkali catalyst to an alcohol solution of a polymer can be cited. An example of a saponification step is described below.
[0073] As the alcohol serving as a solvent for the polymer, for example, methanol, ethanol, butanol, etc. can be used, and methanol can be preferably used. The concentration of the polymer in the alcohol solution can be arbitrarily set, and can be, for example, 10 mass % or more and 80 mass % or less.
[0074] Next, an alkali catalyst is added to the above solution to carry out a saponification reaction. Examples of the alkali catalyst include hydroxides and alkoxides of alkali metals such as sodium hydroxide, potassium hydroxide, sodium methoxide, sodium ethoxide, and potassium methoxide. Among them, sodium hydroxide is preferably used. The amount of the alkali catalyst added is not particularly limited, and is preferably set to 1.0 to 100.0 millimolar equivalents, and more preferably set to 5.0 to 30.0 millimolar equivalents, relative to the polymer. The reaction temperature during saponification is not particularly limited, and is preferably 10 to 70°C, and more preferably 30 to 55°C. The reaction time is also not particularly limited, and can be, for example, 20 minutes or more to 2 hours.
[0075] The saponification degree can be appropriately adjusted according to the application of PVA, and can be, for example, 72 to 99 mol%, preferably 75 to 99 mol%. After the saponification reaction, a washing step and a drying step for removing impurities such as sodium acetate may be performed as necessary.
[0076] <Additives for Oil Well Cement>
[0077] In one embodiment, an additive for oil well cement containing the above-mentioned PVA can be provided, which can be suitably used in cementing oil wells, gas wells, steam wells for geothermal power generation, and the like.
[0078] Cementing during well excavation is the process of injecting cement into the gap between the excavated well and the steel pipe inserted therein. As a method of cementing, the following method is widely used: after mixing cement with various additives such as fluid loss additives in a dry state, slurrying with high-pressure water and injecting by pump.
[0079] If PVA is used as a fluid loss reducing agent, it can reduce the loss of water contained in the cement slurry during cementing (i.e., reduce fluid loss), thereby maintaining the fluidity of the cement slurry. In the case of large fluid loss, the fluidity of the cement slurry is lost, making it difficult to perform adequate cementing.
[0080] Fluid loss evaluation is one of the evaluation items of oil well cement defined by the American Petroleum Institute (API). The test method of fluid loss is described in Recommended Practice for Testing Well Cements, API Recommended Practice 10B-2, April 2013.
[0081] <Cement Composition for Oil Wells>
[0082] In one embodiment, a cement composition for oil wells containing oil well cement and the above-mentioned additive for oil well cement can be provided. The above-mentioned oil well cement may be any cement used for well cementing in oil wells, gas wells, steam wells for geothermal power generation, etc., and is not particularly limited.
[0083] In the above composition, the content of the additive for oil well cement is preferably 0.01 to 10% bwoc, more preferably 0.05 to 5% bwoc. By setting it within such a range, the fluid loss can be effectively reduced. It should be noted that "bwoc" (by weight of cement) refers to the cement weight basis, which means the weight of the additive in the dry state added to the cement composition based only on the solid components of the cement.
[0084] <Cement Slurry for Oil Wells>
[0085] In one embodiment, a cement slurry for oil wells containing oil well cement, the above-mentioned additive for oil well cement, and water can also be provided. In the above cement slurry, the content of water is preferably 20 to 40% by mass.
[0086] The method of making the cement slurry contain the additive for oil well cement is not particularly limited. For example, there may be mentioned a method of mixing the composition containing oil well cement and the additive with water after preparing the composition, a method of mixing oil well cement, the additive, and water without preparing the composition, etc.
[0087] Examples
[0088] Hereinafter, the present invention will be described in more detail based on examples. It should be noted that the examples described below are an example showing representative examples of the present invention, and the present invention is not limited to the following examples.
[0089] <Preparation of PVA>
[0090] [Example 1]
[0091] 100 parts by mass of vinyl acetate, 70.2 parts by mass of methanol (recorded as "initial methanol" in the table), 0.16 parts by mass of triallyl isocyanurate (TAIC) as a polyfunctional monomer, and 5.0×10 of PEROYL NPP (manufactured by NOF Corporation) as an initiator were charged into a polymerization tank equipped with a reflux condenser, a dropping funnel, and a stirrer. -6Parts by mass, and polymerization was carried out at the boiling point while stirring under a nitrogen atmosphere. At the time point when the polymerization rate reached 30%, 26.1 parts by mass of methanol (recorded as "post-added methanol" in the table) was added, and polymerization was carried out until the polymerization rate reached 44%. Next, the unreacted vinyl acetate monomer was removed from the polymerization system to obtain a methanol solution of the polyvinyl acetate-TAIC copolymer.
[0092] A methanol solution of sodium hydroxide (0.008 mol% of sodium hydroxide relative to the copolymer) was added to the obtained methanol solution of the vinyl acetate-TAIC copolymer. Then, a saponification reaction was carried out at 45 °C for 45 minutes to obtain PVA with a saponification degree of 91.3 mol%.
[0093] In addition, in the experiment, it was visually confirmed whether there were insoluble attachments remaining in the system. The case where no attachments were visually confirmed was evaluated as "○" (good), the case where several attachments were visible was evaluated as "△" (bad), and the case where a large number of attachments were visible was evaluated as "×" (NG).
[0094] [Examples 2 - 6, Comparative Examples 1 - 4]
[0095] The input amounts were changed as shown in Table 1 below. Except for this, PVA of Examples 2 - 6 and Comparative Examples 1 - 4 was obtained according to the same procedure as in Example 1. It should be noted that Comparative Examples 2 and 3 reproduced Example 3 and Example 5 of Patent Document 3 respectively. In addition, Comparative Example 4 reproduced Example 5 of Patent Document 4. That is, in the comparative examples, methanol was not added in batches.
[0096] <Measurement of Physical Properties of PVA>
[0097] [Copolymerization Amount, Unsaturation Amount]
[0098] Calculation was carried out according to the above method using a trace total nitrogen analyzer "TN - 2100H" (manufactured by Nittoseiko Analytech Co., Ltd.).
[0099] [Saponification Degree]
[0100] Measurement and calculation were carried out according to the method described in Japanese Industrial Standard JIS K6726:1994 "3.5 Saponification Degree".
[0101] [Average Degree of Polymerization]
[0102] The average polymerization degree was measured and calculated according to JIS K6726:1994 of Japanese Industrial Standards. Before injecting the PVA aqueous solution of about 1 mass % adjusted for the average polymerization degree into the Ostwaldmeter, it was filtered with a 300-mesh (0.045 mm) filter. In addition, the concentration of PVA used in the calculation of the average polymerization degree was used as the value of the concentration after filtration.
[0103] [Viscosity]
[0104] The compositions of the Examples and Comparative Examples prepared as described above were adjusted to 4 mass % aqueous solutions, which were used as samples for viscosity measurement. Using these samples, the viscosity was measured and calculated according to Japanese Industrial Standards JIS K6726:1994 "4.2 Determination of viscosity".
[0105] [Determination of fluid loss]
[0106] The fluid loss reduction effect of PVA was measured according to the fluid loss evaluation method of the American Petroleum Institute (API) standard 10B-2 (April 2013). The specific measurement procedure is as follows.
[0107] PVA and a hardening retarder ("CR-270" manufactured by Flotek Industries) in the amounts listed in the table were blended into G-grade oil well cement at 0.4% bwoc, and mixed with water according to the procedure described in the American Petroleum Institute (API) standard 10B-2 (April 2013) to obtain a cement slurry having a water content of 30% by mass. The obtained cement slurry was placed in a fluid loss evaluation tester "Model 7120" (manufactured by Chandler Engineering), and the test was performed at the temperature listed in the table and under a pressure of 1000 psi according to the procedure described in the American Petroleum Institute (API) standard 10B-2 (April 2013), and the fluid loss was calculated.
[0108] The evaluation was performed at a temperature ranging from 40° C. to 140° C. and a PVA addition amount ranging from 0.4 to 1.2% bwoc as shown in Table 2. In the table, “-” indicates that the fluid loss measurement was not performed.
[0109] [Table 1]
[0110]
[0111] [Table 2]
[0112]
[0113] The results of the examples confirm that the oil well cement additive of the present invention has good fluid loss reduction performance and can be produced without generating solvent-insoluble attachments and without excessively increasing the viscosity in the system. On the other hand, some performance deficiencies were also confirmed in the comparative examples.
[0114] (Note 1)
[0115] A polyvinyl alcohol polymer characterized in that it is obtained by saponifying a copolymer of a vinyl ester monomer and a multifunctional monomer having two or more polymerizable unsaturated bonds in the molecule.
[0116] The average degree of polymerization of the polyvinyl alcohol-based polymer measured by the method described in JIS K 6726:1994 is 3000 to 6000.
[0117] The reaction rate of the polymerizable unsaturated bonds of the polyfunctional monomer is 55 to 75%.
[0118] (Note 2)
[0119] The polyvinyl alcohol polymer according to Appendix 1 is characterized in that the number of polymerizable unsaturated sites of the polyfunctional monomer is 2 to 5.
[0120] (Note 3)
[0121] The polyvinyl alcohol polymer according to Appendix 1 or 2, wherein the amount of polymerizable unsaturated sites in the polyvinyl alcohol polymer is 0.05 to 0.30 mol % based on the total of the vinyl alcohol units and the vinyl acetate units.
[0122] (Note 4)
[0123] The polyvinyl alcohol polymer according to any one of Appendix 1 to 3, wherein the amount of the polyfunctional monomer unit in the polyvinyl alcohol polymer is 0.05 to 0.30 mol % based on the total amount of the vinyl alcohol unit and the vinyl acetate unit.
[0124] (Note 5)
[0125] The polyvinyl alcohol polymer according to any one of appendices 1 to 4, wherein the viscosity of a 4% aqueous solution of the polyvinyl alcohol polymer is 40 to 200 mPa·s.
[0126] (Note 6)
[0127] The polyvinyl alcohol-based polymer according to any one of Appendix 1 to 5, wherein the polyvinyl alcohol-based polymer has a saponification degree of 75 to 99 mol%.
[0128] (Note 7)
[0129] A polyvinyl alcohol-based polymer as described in any one of Appendix 1 to 6, wherein the filter pass rate of a 1.0 mass % aqueous solution of the polyvinyl alcohol-based polymer through a 45 μm mesh is 95 mass % or more calculated on a solid content basis, and the membrane filter pass rate of a 1.0 mass % aqueous solution of the polyvinyl alcohol-based polymer through a 0.45 μm pore size is 5 mass % or less calculated on a solid content basis.
[0130] (Note 8)
[0131] The polyvinyl alcohol polymer according to any one of Appendix 1 to 7, wherein the particle size of the polyvinyl alcohol polymer is 20% by mass or less of a polyvinyl alcohol polymer having a particle size of 75 μm or less and 10% by mass or less of a polyvinyl alcohol polymer having a particle size of 500 μm or more.
[0132] (Note 9)
[0133] An additive for oil well cement comprising the polyvinyl alcohol-based polymer according to any one of Appendix 1 to 8.
[0134] (Note 10)
[0135] A method for producing a polyvinyl alcohol-based polymer, comprising:
[0136] A step of adding an initiator to a mixture of a vinyl ester monomer and a multifunctional monomer having two or more polymerizable unsaturated bonds in the molecule, and performing a first polymerization reaction in an organic solvent until a first polymerization rate is reached;
[0137] After the first polymerization reaction, an organic solvent is added to conduct a second polymerization reaction until a second polymerization rate higher than the first polymerization rate is reached; and
[0138] A step of adding a solution obtained by adding a base catalyst to an organic solvent to a solution of the copolymer of the vinyl ester monomer and the polyfunctional monomer obtained after the second polymerization reaction to carry out a saponification reaction, thereby obtaining a polyvinyl alcohol-based polymer having an average degree of polymerization of 3,000 to 6,000 as measured by the method described in JIS K 6726:1994 and a reaction rate of polymerizable unsaturated bonds of the polyfunctional monomer of 55 to 75%.
Claims
1. A polyvinyl alcohol-based polymer, characterized in that: It is a polyvinyl alcohol polymer obtained by saponifying a copolymer of a vinyl ester monomer and a multifunctional monomer having two or more polymerizable unsaturated bonds in the molecule. The average degree of polymerization of the polyvinyl alcohol-based polymer measured by the method described in JIS K 6726:1994 is 3000 to 6000. The reaction rate of the polymerizable unsaturated bonds of the polyfunctional monomer is 55 to 75%.
2. The polyvinyl alcohol-based polymer according to claim 1, wherein The number of polymerizable unsaturated sites in the polyfunctional monomer is 2 to 5.
3. The polyvinyl alcohol-based polymer according to claim 1 or 2, wherein The amount of polymerizable unsaturated sites in the polyvinyl alcohol polymer is 0.05 to 0.30 mol % based on the total of the vinyl alcohol units and the vinyl acetate units.
4. The polyvinyl alcohol-based polymer according to claim 1 or 2, wherein The amount of the multifunctional monomer unit in the polyvinyl alcohol-based polymer is 0.05 to 0.30 mol % based on the total of the vinyl alcohol unit and the vinyl acetate unit.
5. The polyvinyl alcohol-based polymer according to claim 1 or 2, wherein The viscosity of a 4% aqueous solution of the polyvinyl alcohol polymer is 40 to 200 mPa.s.
6. The polyvinyl alcohol-based polymer according to claim 1 or 2, wherein The saponification degree of the polyvinyl alcohol polymer is 75 to 99 mol%.
7. The polyvinyl alcohol-based polymer according to claim 1 or 2, wherein The 1.0 mass % aqueous solution of the polyvinyl alcohol polymer has a 45 μm filter pass rate of 95 mass % or more in terms of solid content, and a 0.45 μm membrane filter pass rate of 5 mass % or less in terms of solid content.
8. The polyvinyl alcohol-based polymer according to claim 1 or 2, wherein Regarding the particle size of the polyvinyl alcohol-based polymer, the polyvinyl alcohol-based polymer having a particle size of 75 μm or less accounts for 20% by mass or less, and the polyvinyl alcohol-based polymer having a particle size of 500 μm or more accounts for 10% by mass or less.
9. An additive for oil well cement, comprising the polyvinyl alcohol polymer according to claim 1 or 2.
10. A method for producing a polyvinyl alcohol-based polymer, characterized in that: include: A step of adding an initiator to a mixture of a vinyl ester monomer and a multifunctional monomer having two or more polymerizable unsaturated bonds in the molecule, and performing a first polymerization reaction in an organic solvent until a first polymerization rate is reached; After the first polymerization reaction, an organic solvent is added to conduct a second polymerization reaction until a second polymerization rate higher than the first polymerization rate is reached; and A step of adding a solution obtained by adding an alkali catalyst to an organic solvent to a solution of the copolymer of the vinyl ester monomer and the multifunctional monomer obtained after the second polymerization reaction to carry out a saponification reaction, thereby obtaining a polyvinyl alcohol-based polymer having an average degree of polymerization of 3000 to 6000 as measured by the method described in JIS K6726:1994 and a reaction rate of polymerizable unsaturated bonds of the multifunctional monomer of 55 to 75%.
Citation Information
Patent Citations
Additive for slurry, drilling mud, and cement slurry
JP2015196733A
Fluid loss additive with improved rheological properties
WO2007146348A2
Additive for oil well cement and cement slurry using said additive for oil well cement
WO2019163490A1
Poly(vinyl alcohol)-based polymer
WO2022024792A1